Changes in appendicitis treatment during the COVID-19 pandemic – A systematic review and meta-analysis. (November 2021) - Köhler, Franziska; Müller, Sophie; Hendricks, Anne; Kastner, Carolin; Reese, Lena; Boerner, Kevin; Flemming, Sven; Lock, Johan F.; Germer, Christoph-Thomas; Wiegering, Armin
Abstract: Background: During the COVID-19 pandemic in 2020 a decrease of emergency consultations and modification in treatment of numerous medical conditions were observed. Aim of this paper was to evaluate the effect of the COVID-19 pandemic on incidence, treatment strategies, severity, length of hospital stay and time of presentation in adults and children with acute appendicitis. Methods: A systematic literature search of Pubmed, Embase and Cochrane databases was performed, and eligible studies used to perform a meta-analysis. Results: 46 suitable studies were identified with an overall reduction of appendicitis cases by 20.9% in adults and an increase of 13.4% in children. The rate of open appendectomies increased without statistical significance in both groups (adults: 8.5% vs. 7.1%, P = 0.32; children: 7.1% vs. 5.3%, P = 0.13), whereas the rate of antibiotic treatment increased significantly (P = 0.007; P = 0.03). Higher rates of complicated appendicitis were observed in adults (adults: OR 2.00, P < 0.0001; children: OR 1.64, P = 0.12). Time to first consultation did not change significantly (adults: 52.3 vs. 38.5 h – P = 0.057; children: 51.5 vs. 32.0 h – P = 0.062) and length of stay was also not lengthened during the pandemic (adults: 2.9 vs. 2.7 days, P = 0.057; children: 4.2 vs. 3.7 days, P = 0.062). Conclusion: The COVID-19 pandemic of 2020 had major impact on incidence and treatment strategies of acute appendicitis. Results of this meta-analysis might be another hint to support the theory that appendicitis is not a progressive disease and surgeons can safely consider antibiotic therapy for acute uncomplicated appendicitis. Highlights: The overall incidence of acute appendicitis decreased by 20.9% in adults and increased by 13.4% in children. Instead of appendectomy, antibiotic therapy was administered more frequently during the pandemic. There was an significant increase of complicated appendicitis including perforation and abscess in adults. Rate of open surgery, length of stay and time from start of symptoms to presentation in the emergency room did not change.